INTELLANCE 2/EORTC 1410 randomized phase II study of Depatux-M alone and with temozolomide vs temozolomide or lomustine in recurrent EGFR amplified glioblastoma. Issue 5 (20th November 2019) - Van Den Bent, Martin; Eoli, Marica; Sepulveda, Juan Manuel; Smits, Marion; Walenkamp, Annemiek; Frenel, Jean-Sebastian; Franceschi, Enrico; Clement, Paul M; Chinot, Olivier; De Vos, Filip; Whenham, Nicolas; Sanghera, Paul; et al.
Abstract: Background: Depatuxizumab mafodotin (Depatux-M) is a tumor-specific antibody–drug conjugate consisting of an antibody (ABT-806) directed against activated epidermal growth factor receptor (EGFR) and the toxin monomethylauristatin-F. We investigated Depatux-M in combination with temozolomide or as a single agent in a randomized controlled phase II trial in recurrent EGFR amplified glioblastoma. Methods: Eligible were patients with centrally confirmed EGFR amplified glioblastoma at first recurrence after chemo-irradiation with temozolomide. Patients were randomized to either Depatux-M 1.25 mg/kg every 2 weeks intravenously, or this treatment combined with temozolomide 150–200 mg/m 2 day 1–5 every 4 weeks, or either lomustine or temozolomide. The primary endpoint of the study was overall survival. Results: Two hundred sixty patients were randomized. In the primary efficacy analysis with 199 events (median follow-up 15.0 mo), the hazard ratio (HR) for the combination arm compared with the control arm was 0.71 (95% CI = 0.50, 1.02; P = 0.062). The efficacy of Depatux-M monotherapy was comparable to that of the control arm (HR = 1.04, 95% CI = 0.73, 1.48; P = 0.83). The most frequent toxicity in Depatux-M treated patients was a reversible corneal epitheliopathy, occurring as grades 3–4 adverse events in 25–30% of patients. In the long-term follow-up analysis with median follow-up of 28.7 months, the HR for the comparison of the combination arm versus the control arm was 0.66 (95% CI = 0.48, 0.93). Conclusion: This trial suggests a possible role for the use of Depatux-M in combination with temozolomide in EGFR amplified recurrent glioblastoma, especially in patients relapsing well after the end of first-line adjuvant temozolomide treatment. (NCT02343406)